Epigenetics of Meningiomas. (25th May 2015) - Murnyák, Balázs; Bognár, László; Klekner, Álmos; Hortobágyi, Tibor
Abstract : Meningiomas account for one-third of all adult central nervous system tumours and are divided into three WHO grades. In contrast to the relatively well characterized genetic alterations, our current understanding of epigenetic modifications involved in the meningioma-genesis and progression is rather incomplete. Contrary to genetic alterations, epigenetic changes do not alter the primary DNA sequence and their reversible nature serves as an excellent basis for prevention and development of novel personalised tumour therapies. Indeed, growing body of evidence suggests that disturbed epigenetic regulation plays a key role in the pathogenesis of meningiomas. Altered DNA methylation, microRNA expression, histone, and chromatin modifications are frequently noted in meningiomas bearing prognostic and therapeutic relevance. In this review we provide an overview on recently identified epigenetic alterations in meningiomas and discuss their role in tumour initiation, progression, and recurrence.